2021
DOI: 10.21511/ppm.19(1).2021.37
|View full text |Cite
|
Sign up to set email alerts
|

The influence of servant leadership on job satisfaction with individual character as a moderating variable

Abstract: This study aims to investigate the influence of servant leadership on job satisfaction with individual character as a moderating variable. It used a quantitative approach with multiple linear regression analysis. The population of this study were employees of the Central Sulawesi province industry and trade office. It involved 72 samples selected using a purposive sampling technique. The results showed that servant leadership significantly influence job satisfaction with a value of 82.5%. The most significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
3
0
2
Order By: Relevance
“…Many factors can explain why some employees are more engaged with their work than others, but previous research has shown an important role that leadership style plays (Hasanuddin et al, 2021). The results of this study support the findings from Iqbal et al (2020) and Arain et al (2019) who found a positive relationship between servant leadership and individual performance.…”
Section: Discussionsupporting
confidence: 86%
“…Many factors can explain why some employees are more engaged with their work than others, but previous research has shown an important role that leadership style plays (Hasanuddin et al, 2021). The results of this study support the findings from Iqbal et al (2020) and Arain et al (2019) who found a positive relationship between servant leadership and individual performance.…”
Section: Discussionsupporting
confidence: 86%
“…This makes the followers feel that their leaders are genuinely concerned about them. Consequently, it is no surprise that Hasanuddin, Mustainah, and Buntuang (2021) have found relationship between all servant leadership dimensions and the job satisfaction. Moreover, Schneider and George (2011) had found the job satisfaction is related to both servant leadership and organizational commitment.…”
Section: Servant Leadership Job Satisfaction and Organizational Commi...mentioning
confidence: 99%
“…Hence, it is a unique leadership style and thereby followers may feel to reciprocate the gesture. Therefore, it is no surprise that researchers have studied servant leadership together with job satisfaction (Hasanuddin, Mustainah, & Buntuang, 2021), organizational commitment (Winarno, & Hermana, 2021) and employee performance (Sarwar, Cavaliere, Ammar, & Afzal, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian menemukan bahwa individu yang memiliki karakter yang baik, seperti integritas, disiplin, dan rasa tanggung jawab, cenderung mencapai tingkat prestasi kerja yang lebih tinggi dan lebih cepat naik dalam hierarki organisasi (Hasanuddin et al, 2021). Mereka juga lebih mungkin mendapatkan kesempatan promosi dan penghargaan yang lebih besar.…”
Section: Pendahuluanunclassified